BIOLOGICAL ACTIVITIES AFFORDED BY THE EXTRACT FROM RARU BARK TO INHIBIT ACTION OF ALPHA- GLUCOSIDASE ENZYMES - Gunawan Pasaribu; Wasrin Syafii; Latifah K. Darusman (Secretariat of Agency for Standardization of Environment and Forestry Instruments, 2011)
Raru (Shoreabalanocarpoides Sym) signifies one of the tree species that grows widespread in Sumatra Island. Its bark portion is commonly used by local villagers as additional ingredient mixed to nira (sugar palm juice). This addition is intended to make the juice more durable and also to enrich its taste after the juice is previously fermented to become traditional toddy beverage or the so-call “tuak”. Local villagers believe that raru bark can reduce the level of blood sugar. As the relevance, the research was conducted to confirm that the extract from raru bark could afford its biological activities to inhibit alpha-glucosidase enzyme through its characterization, quantification, and isolation of its boactive compound. The extraction was performed using two methods (i.e.reflux and maceration techniques). Result revealed that the bark extract obtained from both techniques contained polyphenol compounds: flavonoid, saponin and tannin. Further, raru-bark extract from the reflux and maceration techniques could inhibit the action of alpha glucosidase enzymes on carbohydrate substrate ( i.e. p -nitrophenil-α-D-glucopyranose), at respectively 90.67% and 97.33%. Meanwhile, the inhibition activities afforded by the patented drug as a control (i.e. glucobay) equaled to 97.05%. Assesment using UV-VIS spectroscopy, showed that the maximum spectrum of bioactive compound in the extract was at the wave length of 288.6 nm. Scrutiny using FTIR spectroscopy could identif y the presence of aromatic groups in the compound, containing -OH, C-H, C=C, C-O and C-H bond types. Analysis using GC-MS exhibited that the compound had molecular weight of 390 with molecular structure as C20H22O8. Ultimately, data analysis scrutiny with the aid of NMR judged the most plausible compound as bioactive was 4-Glucosyl-3, 4’, 5-trihydroxystilbene.